Introducing the Home Learning Environment Questionnaire and examining the profiles of home learning environments in Greece - Krousorati, Katerina; Gregoriadis, Athanasios; Tsigilis, Nikolaos; Grammatikopoulos, Vasilis; Evangelou, Maria (Frontiers in Education, 2022)
The Home Learning Environment (HLE) plays a prominent role in children’s development. Several measures have been developed to assess its quality; however, most of them seem to mainly focus on specific aspects of the HLE construct. The aim of this study was to develop and validate the Home Learning Environment Questionnaire (HLEQ); and to examine the characteristics of the HLE and the HLE profiles using the new instrument in the Greek educational context. The HLEQ is a parent-reported measure addressing both activities and interactions, comprising of six factors that are considered key elements of the HLE: indoor, outdoor, and digital learning activities, warmth/support, conflict, and inconsistent discipline. The development of HLEQ followed a robust methodological approach, including the collection of an initial pool of items, expert review to examine its content validity, and piloting. The HLEQ was administrated to 814 parents (Mage = 37.86 years, SD = 4.84) of children (Mage = 64.12 months, SD = 7.19) attending 84 state funded kindergartens in Greece. A cross-validation approach was used to examine the factor structure of the HLEQ. Exploratory and confirmatory factor analysis and exploratory structural equation modeling procedures were implemented. Latent profile analysis was employed to identify the HLE profiles. Results provided initial support for the factor structure, reliability, and validity of the HLEQ. The HLEQ displayed good psychometric properties for measuring the quality of home learning activities and home learning interactions in the contemporary early HLE. Four HLE profiles were revealed, representing different parent-child interaction patterns during the learning activities. Limitations and implications for policy and practice are discussed.